Hypomyelination and Oligodendroglial Alterations in a Mouse Model of Autism Spectrum Disorder - Graciarena, Mariana; Seiffe, Araceli; Nait-Oumesmar, Brahim; Depino, Amaicha M. (Frontiers in Cellular Neuroscience, 2019)
Autism spectrum disorders (ASD) are neuropsychiatric diseases characterized by impaired social interaction, communication deficits, and repetitive and stereotyped behaviors. ASD etiology is unknown, and both genetic and environmental causes have been proposed. Different brain structures are believed to play a role in ASD-related behaviors, including medial prefrontal cortex (mPFC), Hippocampus, Piriform cortex (Pir), Basolateral Amygdala (BLA) and Cerebellum. Compelling evidence suggests a link between white matter modifications and ASD symptoms in patients. Besides, an hypomyelination of the mPFC has been associated in rodents to social behavior impairment, one of the main symptoms of ASD. However, a comparative analysis of myelination as well as oligodendroglial (OL-) lineage cells in brain regions associated to social behaviors in animal models of ASD has not been performed so far. Here, we investigated whether OL- lineage cells and myelination are altered in a murine model of ASD induced by the prenatal exposure to valproic acid (VPA). We showed an hypomyelination in the BLA and Pir of adult VPA-exposed mice. These results were accompanied by a decrease in the number of OL-lineage cells and of mature OLs in the Pir, in addition to the mPFC, where myelination presented no alterations. In these regions the number of oligodendrocyte progenitors (OPCs) remained unaltered. Likewise, activation of histone deacetylases on OL-lineage cells in adulthood showed no differences. Overall, our results reveal OL-lineage cell alterations and hypomyelination as neuropathological hallmarks of ASD that have been overlooked so far.